The role of the hippocampus in object discrimination based on visual features - Levcik, David; Nekovarova, Tereza; Antosova, Eliska; Stuchlik, Ales; Klement, Daniel (Neurobiology of learning and memory, 2018)
The role of rodent hippocampus has been intensively studied in different cognitive tasks. However, its role in discrimination of objects remains controversial due to conflicting findings. We tested whether the number and type of features available for the identification of objects might affect the strategy (hippocampal-independent vs. hippocampal-dependent) that rats adopt to solve object discrimination tasks. We trained rats to discriminate 2D visual objects presented on a computer screen. The objects were defined either by their shape only or by multiple-features (a combination of filling pattern and brightness in addition to the shape). Our data showed that objects displayed as simple geometric shapes are not discriminated by trained rats after their hippocampi had been bilaterally inactivated by the GABAA-agonist muscimol. On the other hand, objects containing a specific combination of non-geometric features in addition to the shape are discriminated even without the hippocampus. Our results suggest that the involvement of the hippocampus in visual object discrimination depends on the abundance of object's features.
Keywords: muscimol; Behavior, Animal; vnímání tvaru; rozpoznávání obrazu; Form Perception; Rats; Pattern Recognition, Visual; GABA-A Receptor Agonists; generalizace (psychologie); potkani Long-Evans; hipokampus; mužské pohlaví; agonisté receptorů GABA-A; Generalization, Psychological; krysa rodu Rattus; Object discrimination; zvířata; Operant conditioning; diskriminační učení; Muscimol; Discrimination Learning; chování zvířat; Rats, Long-Evans; Visual discrimination; operantní podmiňování; Conditioning, Operant; Male; Hippocampus; Animals